2019
DOI: 10.2147/ccid.s195733
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fine needle aspiration cytology as a preliminary diagnostic tool in chondroid syringoma: a case report and review</p>

Abstract: We report a case of chondroid syringoma (CS) in a 44-year-old male. He presented with a firm asymptomatic nodule in his left upper lip of 2-year duration. The initial clue to the diagnosis was made on fine needle aspiration cytology (FNAC), and a final diagnosis was based on histopathological examination. The case highlights the importance of FNAC in providing clues to the diagnosis of suspected cases of chondroid syringoma before performing large excisions and repair, which would require more skill and time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Similarly, Stout and Gorman (10) reported only 2 out of 134 cases (1.5%) of CS in the head and neck region occurred on the lower lip. Consistent with previous reports (4,10), our professional literature search indicated that CS of the lower lip remains rare with only 4 out of 42 cases (9.5%) reported in the identified articles on CS of the lips (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Stout and Gorman (10) reported only 2 out of 134 cases (1.5%) of CS in the head and neck region occurred on the lower lip. Consistent with previous reports (4,10), our professional literature search indicated that CS of the lower lip remains rare with only 4 out of 42 cases (9.5%) reported in the identified articles on CS of the lips (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 90%
“…O padrão ouro para diagnóstico é a biópsia excisional completa da lesão e exame histopatológico. Embora exista relato de abordagem diagnóstica por punção de agulha fina, esta modalidade ainda é inexpressiva (SYED et al, 2019).…”
Section: Discussionunclassified
“…Besides that, mixed tumor or known as chondroid syringoma share similarities with pleomorphic adenoma. The differences between both are, pleomorphic adenoma is a mixed tumor that arises from salivary glands and chondroid syringoma are mixed tumor arise from the sweat glands [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Other consequences of the slowly growing mass over the nasal site are nasal obstruction, aesthetically disfigured, pain, and risk of infection. Presently, there is a multitude of treatment options for chondroid syringoma such as carbon dioxide laser (CO2 laser), electrodesiccation, and vaporization with argon or CO2 laser [8]. However, complete surgical excision with negative margins is the preferred treatment choice [3,6] to prevent a high rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%